P156 Neutrophil and redox dependent proteolysis of bone morphogenetic protein 9: potential role in the pathogenesis of pulmonary arterial hypertension. (14th November 2013) - Li, W; Hoenderdos, K; Salmon, RM; Upton, PD; Condliffe, AM; Chilvers, ER; Morrell, NW
Abstract : Introduction: A critical reduction of bone morphogenetic protein type II receptor (BMPRII) in the pulmonary circulation, either due to the genetic loss-of-function mutations, heightened inflammation or prolonged hypoxia, is one of the major causes behind pulmonary arterial hypertension (PAH), a fatal disease with poor prognosis. BMPRII is highly expressed in the vascular endothelium and undergoes rapid turnover. Bone morphogenetic protein 9 (BMP9), the only active circulating BMP, signals via endothelial BMPRII, inducing BMPRII expression and maintaining endothelial homeostasis. Although BMPRII function has been studied extensively, factors that regulate BMP9 stability and activity remain unclear. Objective: To investigate how BMP9 activity and stability are regulated and whether this regulation plays a role in pulmonary arterial hypertension. Results: Two forms of BMP9 dimer could be co-purified, with (D-form) or without (M-form) intermolecular disulphide bond. M- and D-forms BMP9 are interchangeable with redox potential, but have different stability. While the M-form is more susceptible to redox-dependent cleavage and proteases present in serum, the D-form is a preferred substrate for neutrophil elastase. Freshly isolated human peripheral blood neutrophils, when activated by hypoxia or inflammatory stimuli, released elastase that cleaved BMP9 effectively. Conclusions and Discussions: This study demonstrates a novel proteolytic regulation of BMP9 under physiological and pathological conditions, suggesting neutrophil elastase could be a potential link between inflammation/hypoxia and BMPRII signalling, and the recognised benefits of elastase inhibition in rodent models of PAH may be due in part to reduced degradation of BMP9 and preservation of endothelial BMPR-II signalling.